PENGEMBANGAN MEDIA BIG BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMPREDIKSI BACAAN ISI CERITA PADA KELAS IV SDN NO. 173324 LUMBANJULU LINTONGNIHUTA - Vivi Sinaga; Dody F. P. Ambarita; Nurmayani; Tiarnita Siregar; Apiek Gandamana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading is a fundamental skill that is crucial for elementary school students to develop, particularly in understanding and predicting the content of reading material. Therefore, engaging and interactive learning media are needed to help students improve this ability. One such medium is the Big Book, which presents large text and illustrations, making it easier for students to actively read together. This study aims to: Determine the feasibility, practicality, and effectiveness of the Big Book media developed for fourth graders of SDN No. 173324 Lumbanjulu Lintongnihuta. The research conducted by the researcher is a type of research and development (R&D). The research took place at the fourth graders of SDN No. 173324 Lumbanjulu Lintongnihuta, located in Lintongnihuta District, Humbang Hasudutan Regency. The instruments used in this study were validation sheets, questionnaires, and tests. Product validation was conducted by one design/media expert and one material expert. The results of the study indicate that the developed big book media is valid/feasible, practical, and effective. Furthermore, the trial results showed a significant increase in pre- and post-test scores and high student learning activity, indicating that this media is suitable for use as an innovative learning tool in elementary schools.